Fabrication of Integrated Copper‐Based Nanoparticles/Amorphous Metal–Organic Framework by a Facile Spray‐Drying Method: Highly Enhanced CO2 Hydrogenation Activity for Methanol Synthesis. Issue 41 (2nd September 2021) - Mitsuka, Yuko; Ogiwara, Naoki; Mukoyoshi, Megumi; Kitagawa, Hiroshi; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Haneda, Masaaki; Kawaguchi, Shogo; Kubota, Yoshiki; Kobayashi, Hirokazu
Abstract: We report on Cu/amUiO‐66, a composite made of Cu nanoparticles (NPs) and amorphous [Zr6 O4 (OH)4 (BDC)6 ] (amUiO‐66, BDC=1, 4‐benzenedicarboxylate), and Cu‐ZnO/amUiO‐66 made of Cu‐ZnO nanocomposites and amUiO‐66 . Both structures were obtained via a spray‐drying method and characterized using high‐resolution transmission electron microscopy, energy dispersive spectra, powder X‐ray diffraction and extended X‐ray absorption fine structure. The catalytic activity of Cu/amUiO‐66 for CO2 hydrogenation to methanol was 3‐fold that of Cu/crystalline UiO‐66. Moreover, Cu‐ZnO/amUiO‐66 enhanced the methanol production rate by 1.5‐fold compared with Cu/amUiO‐66 and 2.5‐fold compared with γ‐Al2 O3 ‐supported Cu‐ZnO nanocomposites (Cu‐ZnO/γ‐Al2 O3 ) as the representative hydrogenation catalyst. The high catalytic performance was investigated using in situ Fourier transform IR spectra. This is a first report of a catalyst comprising metal NPs and an amorphous metal–organic framework in a gas‐phase reaction. Abstract : We report on a first demonstration for a catalyst comprising metal NPs and amorphous MOF in a gas‐phase reaction. Cu/amorphous UiO‐66 exhibited 3‐fold catalytic activity for CO2 hydrogenation into methanol over Cu/crystalline UiO‐66. Amorphous UiO‐66 coating on Cu‐ZnO nanocomposites showed 1.5‐fold catalytic activity enhancement over that of Cu/amorphous UiO‐66.